Análise do comportamento mecânico a quente do aço inoxidável super duplex UNS S32760 através de mapas de processamento - Dias, Clayton Pereira (Universidade Federal de São Carlos, 2013)
The need for materials with higher mechanical and corrosion resistance in corrosive environments, such as in oil extraction in saline media, paper and pressure vessel industry, has led to the use of stainless steel Super Duplex. The manufacture of these materials involves the step of heat processing, whose performance depends on the hot workability of the material. In this paper we investigate whether the processing conditions in which super duplex stainless steel UNS S32760 can be worked and the work area in which the material can fail. The physical simulation was performed by means of hot torsion testing. The tests were performed at temperatures ranging from 900°C to 1200°C and strain rates of 0.01 s-1 to 10 s-1. The evolution of strain rate sensitivity of the flow stress(m) at all temperatures investigated in strain of 0.25, 0.5, 0.75 and 1 was determined. After obtaining the values of m for each deformation condition, the values of the efficiency of power dissipation (ῃ) were calculated and applying a criterion of instability (ξ) Processing maps were constructed. Using these maps, we discuss the effects of deformation conditions on the efficiency of power dissipation and the instability of plastic material. The domains of processing maps with the observed microstructures and aspects of plastic flow curves were related.
Analysis of the mechanical behavior of hot super duplex stainless steel UNS S32760 through processing maps
Keywords: Metalurgia; Trabalhabilidade a quente; Mapas de processamento; Super duplex; UNS S32760; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA